Implementing Changes in Institutions to Improve Young Children's Development - Groark, Christina J. (2011)
An estimated 8 million children, mostly birth to approximately 6–8 years of age, live in institutions worldwide. While institutional environments vary, certain characteristics are common, including relatively large groups; high children:caregiver ratios; many and frequently changing caregivers; homogeneous grouping by age and disability status; periodic graduations to new groups of peers and caregivers; and an “institutional style of caregiving” that minimizes talking, provides rather dispassionate perfunctory care, and offers little warm, sensitive, contingently-responsive caregiver-child interactions. The development of children in residence is usually delayed, sometimes extremely so, in every physical and behavioral domain. Although efforts are being made in many countries to care for children without permanent parents in family environments (e.g., domestic adoption, foster and kinship care, reunification with biological parents), it is not likely that transitions to family alternatives will be completed in all countries in the near future; thus, institutions are likely to exist for many years if not decades. But institutions need not operate in the current manner; they can be modified to be substantially more family-like in structure and in the behavior of caregivers. Research indicates that when such changes are made the development of children, both typically developing and those with special needs, is improved substantially. Based on the available literature and the authors' experience, this paper describes steps that can be taken to implement such changes in residential institutions for infants and young children.